The Influence of Green Innovation Performance on Corporate Advantage in Taiwan - Chen, Yu-Shan (Journal of business ethics, 2006)
The purpose of this study was to explore whether the performance of the green innovation brought positive effect to the competitive advantage. This study found that the performances of the green product innovation and green process innovation were positively correlated to the corporate competitive advantage. Therefore, the result meant that the investment in the green product innovation and green process innovation was helpful to the businesses. This study argued that the businesses should cognize the correct value and positioning of the green innovation.